Islam as a Science: Ontology, Epistemology and Ethics - Riky Supratama; Aprilia Putri Hapsari; Mega Melani Ramadani; Riyan Hidayat (Yayasan Azhar Amanaa Yogyakarta, 2023)
Speaking philosophical concepts of any field of science, including Islamic education focused on ontology, epistimology and axiology of science. The strengthening of any discipline is strongly determined by these three things. It means that the criteria of a science are determined by the three objectives of the study of philosophy. In connection with these issues, this paper aims to elaborate the concepts of Islam and science with the main focus on ontology, epistimology and axiology of education. In addition, this writing is expected to be useful for further understanding of studies on the relationship of Islam with science. This research is included in the library research, that is, research that limits research and data search only through library collections without requiring research and field data. In this research, researchers use qualitative research methods. In the library research that uses qualitational methods, they take the necessary data from sources such as books, journals, articles.